The SAGE encyclopedia of food issues - Albala, Ken, 1964- (Thousand Oaks, California : SAGE Publications, 2015)
In contrast to the existing reference works on the topic of food that tend to fall into the categories of cultural perspectives, this carefully balanced academic encyclopedia focuses on social and policy aspects of food production, safety, regulation, labeling, marketing, distribution, and consumption. It explores the topic of food across multiple disciplines within the social sciences and related areas including business, consumerism, marketing, and environmentalism.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on November 12, 2015).
Keywords: Food -- Encyclopedias